Electron transport parameters in CO2: a comparison of two experimental systems and measured data. (22nd October 2020) - Vass, Máté; Egüz, Eda; Chachereau, Alise; Hartmann, Péter; Korolov, Ihor; Hösl, Andreas; Bošnjaković, Danko; Dujko, Saša; Donkó, Zoltán; Franck, Christian M
Abstract: Two experimental apparatuses used to obtain electron transport coefficients in gases are compared based on measurements in CO2 over a wide range of E / N -values. The operation principles of the two experimental systems as well as their data acquisition methods are different. One operates under the time of flight (TOF) principle, where the transport coefficients are obtained by fitting the theoretical form of the electron density of a swarm in an unbounded region, n ( x,   t ), to the measured current at different values of the drift length, I ( L,   t ). The other experimental apparatus operates in the Pulsed Townsend (PT) mode, where the electron transport coefficients are obtained by fitting the spatial integral of n ( x,   t ) over the drift region to the measured, time-dependent current signal, I ( t ). In both apparatuses, the measured E / N range was extended as much as possible to allow a large overlap for the comparison of the results. The bulk drift velocity, W, obtained by the two systems agrees well (within a few %) over a wide range of E / N values (100 Td ≤ E / N ≤ 1000 Td). The agreement between the data sets for the longitudinal component of the bulk diffusion tensor, D L, is less satisfactory, the TOF data show systematically higher values (by 10–50% depending on E / N ) than the PT measurements. Significant differences are also found below 100 Td in case of the effective ionisation frequency, ν e f f, and the (steady state) Townsend ionisation coefficient, α e f f, where the TOF apparatus is unable to give accurate results. Our comparison justifies the correctness of the measured data over the range of agreement and also indicates the interval in E / N where the data obtained by each of the experimental systems can be taken to be reliable. The limits of the operating regimes of the two setups, stemming from the hardware and from the physical limits, are discussed.